Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar IPAS Materi Wujud Zat dan Perubahannya Pada Siswa Kelas IV MI/SD - Marniati Kadir; Lusiana Amanda Lestari; Sheilla Oktaviani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aimed to improve students' learning outcomes on the topic of states of matter and their changes through the implementation of the Problem-Based Learning model. This classroom action research was conducted in two cycles. The results showed that learning mastery increased from 16.67% in the pre-cycle to 66.67% in Cycle I and 83.33% in Cycle II. The implementation of PBL also improved students’ participation, collaboration, and problem-solving abilities during the learning process.